viralFlye: assembling viruses and identifying their hosts from long-read metagenomics data - Antipov, Dmitry; Rayko, Mikhail; Kolmogorov, Mikhail; Pevzner, Pavel A. (Genome Biology, 2022)
Although the use of long-read sequencing improves the contiguity of assembled viral genomes compared to short-read methods, assembling complex viral communities remains an open problem. We describe the viralFlye tool for identification and analysis of metagenome-assembled viruses in long-read assemblies. We show it significantly improves viral assemblies and demonstrate that long-reads result in a much larger array of predicted virus-host associations as compared to short-read assemblies. We demonstrate that the identification of novel CRISPR arrays in bacterial genomes from a newly assembled metagenomic sample provides information for predicting novel hosts for novel viruses.